CESSIE DALAM TINJAUAN HUKUM ISLAM - Sup, Devid Frastiawan Amir (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-undangan, Ekonomi Islam, 2019)
Cessie is the submission of accounts receivable in the name regulated in Article 613 of the Civil Code. Cessie in principle is the sale and purchase of receivables, but in its development the cessie can also be used as collateral for debt. In Islamic law, detailed discussion of cessie has not yet existed, but in general the issue of accounts payable has been discussed in the hawalah contract. In the DSN-MUI fatwas cessies are categorized as active subjective innovations or forms of subrogation accompanied by compensation. On the other hand, conceptually, cessie, subrogation and innovation are different. From this description, this research will discuss about cessie in Islamic law review with hawalah approach. The research method used is qualitative-descriptive-literature. The conclusion obtained from this study. (1) Cessie requirements according to the Civil Code have not fulfilled the entire requirements for the formation of the contract contained in hawalah. (2) Cessie in the sale and purchase of receivables is included in hawalah haqq. (3) Cessie as debt collateral is included in hawalah haqq based on kafalah (guarantee). In the case of retro cessie, Hanafi scholars allow while Shafi'i scholars do not allow